MANAJEMEN JARINGAN KOMPUTER DENGAN MENGGUNAKAN MIKROTIK ROUTER (COMPUTER NETWORK MANAGEMENT USED WITH MICROTIC ROUTER) - Sujalwo, Sujalwo (Universitas Muhammadiyah Surakarta, 2011)
This study starts from making observations or collecting data about the condition of computer networks at the Faculties in the distribution of bandwidth and autentication. At the testing stage, it uses a simulation with 3 users in infrastructure and ad?hoc. Hotspot user authentication used to restrict the number of users that use wireless facilities. Speed Internet access becomes faster with the fair distribution of bandwidth for users. Mikrotik is a reliable operating system, not only because safety data are difficult to penetrate, but also router can be used for offices, cafes etc. With the hotspot usage management, it will speed up users to conduct their activities with a large bandwidth which is large enough.?